1991
DOI: 10.1093/ajcn/53.6.1522s
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in US Hispanic populations

Abstract: Previous studies showed that Hispanics have higher levels of overweight and obesity than do US whites. The Hispanic Health and Nutritional Examination Survey (1982-1984) provides the basis for examining the physical characteristics of this population on a wider scale than previously possible. Data for body mass index (BMI; weight/height2) and triceps and subscapular skinfold thicknesses were examined for the 7052 Mexican Americans, 1307 Cubans, and 2690 Puerto Ricans for whom each of these measurements were av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…And an earlier analysis of BMI and SES using HHANES found a weak positive association of BMI with poverty index when obese subjects (95 percentile of NHANES II reference values) were compared to the non-obese using logistic regression. 13 In sum, this and other studies indicate that the in¯uences of earned (income) and attained (education) social status on BMI in US Hispanics is weak. One possible explanation for the lack of a stronger relationship between income and BMI may be the limited income distribution in this population.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…And an earlier analysis of BMI and SES using HHANES found a weak positive association of BMI with poverty index when obese subjects (95 percentile of NHANES II reference values) were compared to the non-obese using logistic regression. 13 In sum, this and other studies indicate that the in¯uences of earned (income) and attained (education) social status on BMI in US Hispanics is weak. One possible explanation for the lack of a stronger relationship between income and BMI may be the limited income distribution in this population.…”
Section: Discussionmentioning
confidence: 60%
“…In the current investigation, compared to the minor association with demographic and SES indicators in all three Hispanic groups, indicators of acculturation were more strongly associated with BMI but only among Mexican Americans. Previous studies of overweight and obesity in Hispanics have attempted to measure acculturation using measures of language 13 and multidimensional scales 6±9 with con¯icting results. However, the San Antonio Heart Study, 24 the present analysis, and others 28 suggest that when adequate measures are available, BMI is associated with acculturation in Mexican Americans even after controlling for demographic and socioeconomic variables which is not the case for Cuban Americans or Puerto Ricans.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of obesity among Hispanic-American adults compared to other groups has been well-documented. 22,23 Much of the work examining the weight status of Hispanic children has been undertaken among Mexican-Americans, who are reported to be relatively shorter and heavier compared to non-Hispanic whites and blacks of all ages. 24,25 By contrast, the greater likelihood of overweight in the NYC Hispanic group was observed, despite the fact that their average height-for-age exceeded the norms in the reference population and was comparable to that of NYC white non-Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Mexican Americans were selected for study because of the reported higher prevalence of obesity, diabetes, and insulin resistance compared to nonHispanic white or black people. 11 Serum ferritin levels were similar in Hispanic and non-Hispanic white people in NHANES II. 12 The study was restricted to men to eliminate confounding by gender, pregnancy, menopause, parity, oral contraceptives or female hormone replacement therapy and reduce possible confounding by iron de®ciency and iron therapy.…”
Section: Introductionmentioning
confidence: 88%